2009
DOI: 10.1007/s11627-009-9192-z
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Teucrium fruticans L., an ornamental and medicinal plant

Abstract: An efficient protocol for in vitro propagation of the valuable ornamental and medicinal plant Bush germander (Teucrium fruticans L.) was developed through axillary shoot proliferation. A Murashige and Skoog agar medium supplemented with benzylaminopurine (6.6 μM), α-naphthaleneacetic acid (0.053 μM), and sucrose (3%) significantly improved the production of multiple shoots directly from nodal segment explants, resulting in an average of 2.8 shoots per segment with an average of 6.8 nodes per shoot that would b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…In agreement, Prathanturarug et al (2012) found that IBA was superior to NAA in terms of root induction percentage and number of roots per shoot with S. hutanguriana regenerated shoots after 8 weeks in culture. A similar trend was also observed for other species including Centella asiatica (Tiwari et al 2000), Boscia senegalensis (Khalafalla et al 2011), Pappea capensis (Mngomba et al 2007) and Teucrium fruticans (Frabetti et al 2009). …”
Section: Discussionsupporting
confidence: 79%
“…In agreement, Prathanturarug et al (2012) found that IBA was superior to NAA in terms of root induction percentage and number of roots per shoot with S. hutanguriana regenerated shoots after 8 weeks in culture. A similar trend was also observed for other species including Centella asiatica (Tiwari et al 2000), Boscia senegalensis (Khalafalla et al 2011), Pappea capensis (Mngomba et al 2007) and Teucrium fruticans (Frabetti et al 2009). …”
Section: Discussionsupporting
confidence: 79%
“…The rooting treatments consisted of full-and halfstrength MS medium supplemented with 0.0 to 24.6μM IBA (Table 3). In previous reports also, IBA proved to be the best for root regeneration of M. dioica (Hoque et al 2007;Hoque et al 1995;Nabi et al 2002;Karim and Ahmed 2010) and had marked effect on rooting of many species such as Centella asiatica (Tiwari et al 2000;Banerjee et al 1999), and Teucrium fruticans L. (Frabetti et al 2009). MS medium strength had significant impact on frequency of root induction, number of roots, and root length.…”
Section: Root Induction and Acclimatizationmentioning
confidence: 88%
“…Nodal segments are preferred explants for micropropa- gation due to presence of preexisting meristems, which can be developed easily into shoots while maintaining clonal fidelity (Frabetti et al 2009). Season of explants collection markedly influences the establishment, growth and regeneration characteristics of in vitro cul- tures.…”
Section: Discussionmentioning
confidence: 99%